2016
DOI: 10.1038/srep27742
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Dementia Assessed by Temporal Correlations of Physical Activity: Results From a 3.5-Year, Longitudinal Randomized Controlled Trial

Abstract: Cross-sectional studies show that activity fluctuations in healthy young adults possess robust temporal correlations that become altered with aging, and in dementia and depression. This study was designed to test whether or not within-subject changes of activity correlations (i) track the clinical progression of dementia, (ii) reflect the alterations of depression symptoms in patients with dementia, and (iii) can be manipulated by clinical interventions aimed at stabilizing circadian rhythmicity and improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 51 publications
2
72
0
1
Order By: Relevance
“…et al (53) and Snitz et al (54) Ginkgo biloba USA Global composite score (P = 0•03), verbal memory (P = 0•007) and TICS (P = 0•04) scores improved compared with placebo but only in participants that had previously participated in PHS1 (aspirin study) Hu et al (57) Melatonin The Netherlands Double-blind, placebocontrolled RCT Therefore it is difficult to draw broad conclusions from this study. The initial cognitive testing was conducted face to face; however, the end point tests were performed over the phone, potentially limiting the utility of these findings.…”
Section: Dekoskymentioning
confidence: 88%
See 2 more Smart Citations
“…et al (53) and Snitz et al (54) Ginkgo biloba USA Global composite score (P = 0•03), verbal memory (P = 0•007) and TICS (P = 0•04) scores improved compared with placebo but only in participants that had previously participated in PHS1 (aspirin study) Hu et al (57) Melatonin The Netherlands Double-blind, placebocontrolled RCT Therefore it is difficult to draw broad conclusions from this study. The initial cognitive testing was conducted face to face; however, the end point tests were performed over the phone, potentially limiting the utility of these findings.…”
Section: Dekoskymentioning
confidence: 88%
“…Variation between different stages of cognitive impairment across the included trials makes it difficult to make conclusions regarding the overall usefulness of the nutraceuticals. Only seven studies in this review included individuals with dementia (44,47,52,(57)(58)(59) , and three included studies (11,36,46) used individuals with MCI. Certainly, there is difficulty in conducting trials in individuals with cognitive impairment and several studies in this review required caregiver assistance or approval to participate from a proxy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that gaps identified in data recordings (see 2.2 Data collection and pre-processing) were skipped when performing the detrended fluctuation analysis to avoid any potential effects of interpolating missing data and/or manipulating the signal (e.g., stitching the rest data after removing the missing data) on F( n ) [ 10 ]. Previous studies showed that cognitive impairment in patients with dementia is associated with smaller α at time scales < ~ 90 minutes [ 11 ]. Thus, we quantified α at time scales between 1.25 and 90 minutes in this study ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous cross sectional study revealed that FR in motor activity is degraded with aging and in Alzheimer’s disease (AD) [ 10 ], and in a short longitudinal study, we found that the degradation of FR in motor activity over time is associated with cognitive decline in very old adults with dementia [ 11 ]. The goal of the present study is to determine whether FR perturbation at baseline in older individuals without dementia is associated with increased risk of the development of Alzheimer’s dementia and mild cognitive impairment (MCI) and rate of cognitive decline.…”
Section: Introductionmentioning
confidence: 99%